ANATOMICAL STUDY OF SOME TAXA OF THE GENUS Anchusa L. IN IRAQ - احمد مي (Iraqi Journal of Science, 2024)
Anatomical study was carried out on the taxa of the genus Anchusa L. including A. aucheri DC. , A. aegyptiaca DC. , A. italifolia Almusawi and Addi , A. strigosa spp. Strigosa Labill. , A. italica var. microcalyx Almusawi and Addi , A. italica var. italica Retz.Vascular tissue of the stem was found to be cylindrical shape in all taxa. internal phloem was reported the first time in the cross section of the stem in addition to the External phloem.Mesophyll of the leaf was found to be isobilateral in all taxa. Shape of the cross section of leaf midrib and the area of vascular tissue of the stem were found to be variable in some species and other taxa could be used as a good taxonomic characters of the test taxa.